Prove that sin y*cos (x - y) + cos y*sin(x - y) = sin x

### 1 Answer | Add Yours

The identity `sin y*cos (x - y) + cos y*sin(x - y) = sin x` has to be proved.

Use the relation `sin a*cos b = (1/2)(sin (a - b) - sin(a + b))`

`sin y*cos (x - y) + cos y*sin(x - y)`

=> `(1/2)(sin (y - x + y) + sin(y + x - y)) + (1/2)*sin(x - y - y) + sin(x - y + y))`

=> `(1/2)(sin (2y - x) + sin x + sin(x - 2y) + sin x)`

=> `(1/2)(sin (2y - x) + sin x - sin(2y - x) + sin x)`

=> `(1/2)(sin x + sin x)`

=> `sin x`

**This proves that **` sin y*cos (x - y) + cos y*sin(x - y) = sin x`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes